Argentimetric assay of ranitidine in bulk drug and in dosage forms - Basavaiah, Kanakapura; Somashekar, Bankavadi Chikkaswamy (Eclética Química, 2007)
Two simple, rapid and cost-effective methods based on titrimetric and spectrophotometric techniques are described for the assay of RNH in bulk drug and in dosage forms using silver nitrate, mer- cury(II)thiocyanate and iron(III)nitrate as reagents. In titrimetry, an aqueous solution of RNH is treated with measured excess of silver nitrate in HNO 3 medium, followed by determination of unreacted silver nitrate by Volhard method using iron(III) alum indicator. Spectrophotometric method involve the addi- tion a known excess of mercury(II)thiocyanate and iron(III)nitrate to RNH, followed by the measurement of the absorbance of iron(III)thiocyante complex at 470 nm. Titrimetric method is applicable over 4-30 mg range and the reaction stoichiometry is found to be 1:1 (RNH: AgNO 3 ). In the spectrophotometric method, the absorbance is found to increase linearly with concentration of RNH which is corroborated by the correlation coefficient of 0.9959. The system obey Beer’s law for 5-70 μg mL -1 . The calculated apparent molar absorptivity and sandell sensitivity values are found to be 3.27 × 10 3 L mol -1 cm -1 , 0.107 μg cm -2 respectively.